(3agQSJs - (3GdHfGfj , MeOhf Hf eMeO HfGfj Hf YHO GdSdGe, CHh YHO Gddg,J (B1163 (3g` s
(3ChdgG (B:s
(3hHYO deG MddJ MQe ecI GdeTQaI dbjJ gfGc ef TeQ ai fHGgI GdYde Yf SGYO GdYfGjI aOYGfi YRege dbQGAg eG JjSQ ef GdcJH GdMOjKjI s
(3BNQgG (B:s
(3Jhai QMeg Gddg ai SfI Kfjf hCQHYjf heGFI hCda hgh ef CcGHQ JdGejP GdTjN s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B19s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B205 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B168s
(3Odjd eDQN GdeZQH (B- (3U (B355 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B318 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(922 (3c(B) s
Keywords: (3GdJGQjNs